Meaning-making in the academic advising relationship: reflections on student success - Cole, Helena Elizabeth (My University, 2025)
This phenomenological study sought to explore how first-year exploratory majors made meaning of their academic advising experiences. Using the literature surrounding meaning-making framed within the relational component of NACADA: The Global Community for Academic Advising’s core competency model, it interrogated the role that academic advising, and in particular the advisor/advisee relationship plays in a student’s “successful” college experience. Significant to this inquiry was the challenge in defining “student success;” what may contribute to this challenge is the presence of two different, but at times overlapping constructs—that of student success and institutional success—creating a conundrum for any further exploration of what constitutes that “successful” experience. This qualitative study used semi-structured interviews and a reflective questionnaire, as well as a brief online document analysis, to explore the lived experiences of first-year students who were advised by primary-role advisors as exploratory major students in the first and second quarters of attending a four-year public university. Initial exploration and analysis of the data from the interviews did not reveal significant meaning-making experiences on the part of the participants (the focus being more on sense-making); however, answers to the reflective questionnaire indicated that the first interview may have caused participants to think more deeply about their advising experiences and the relationship they had with their advisors. Reflections on the findings of this study, as well as the research process itself—the story of the story—reveal more questions than answers. This further challenges the academic advising community, and perhaps higher education in general, to continue to explore and yes, even make-meaning of, their approaches to the student success conundrum.
Keywords: Academic advising; Advising relationship; Exploratory majors; Meaning-making; Student success